Where hope prevails [large type] - Oke, Janette, 1935-; Logan, Laurel Oke (Oke, Janette, 1935- Return to the Canadian West, 2016)
Elizabeth Thatcher's return to Coal Valley after a long summer with family back east is full of surprises. She will have to decide between her teaching position in the valley and her Royal Canadian Mounted Policeman, Jarrick Thornton.